A STUDY ON GENRE BASED APPROACH IN TEACHING READING TO INDONESIAN EFL LEARNERS - Rangga Mega Putra (Universitas Nahdlatul Ulama Lampung, 2019)
The implementation of genre-based approach in EFL teaching has been increasingly attracting many EFL teachers’ attention. This study aimed at investigating the implementation of Genre-Based Approach in teaching and learning process of reading skill at SMPN 1 Purbolinggo. This study was descriptive qualitative. Thetechniques of collecting the data were observation, interviews and documentation. The data was analyzed by referring to theory of the stages of genre-based approach developed by Feez and Joyce., (1998). The total of the sample of this study was 33 students in the seventh grade of SMPN 1 Purbolinggo. The findings showed that the English teacher still had some weakness in implementing genre-based approach. Moreover, the students still had many difficulties in generic structure and social function of the text. Keywords: EFL learners, Ganre Based Approach, Reading skill.